2016
DOI: 10.1080/14656566.2016.1232396
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular therapies for osteoarthritis

Abstract: Challenges in osteoarthritis therapy research are fundamentally related to the complexity of the pathological mechanisms of osteoarthritis. Novel drugs offer hope in a disease with limited medical therapy options. Whether these future intra-articular therapies will provide clinically meaningful benefits, remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 136 publications
0
26
0
Order By: Relevance
“…Disease progression is usually slow but can ultimately lead to joint failure with pain and disability [ 35 , 36 ]. Current therapies only relieve the symptoms, but cannot stop or reverse cartilage degeneration and destruction [ 37 , 38 ] . Previous studies showed that MSC exosomes, which contain miRNAs, mRNAs, and proteins, are likely to be important mediators in cell–cell communication to induce changes in cell functions and processes [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression is usually slow but can ultimately lead to joint failure with pain and disability [ 35 , 36 ]. Current therapies only relieve the symptoms, but cannot stop or reverse cartilage degeneration and destruction [ 37 , 38 ] . Previous studies showed that MSC exosomes, which contain miRNAs, mRNAs, and proteins, are likely to be important mediators in cell–cell communication to induce changes in cell functions and processes [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by progressive articular cartilage destruction and synovitis 42 , 43 . Current therapies attempt to relieve the symptoms, but they cannot stop or reverse the ongoing cartilage degeneration 4 , 44 . The ideal treatment aiming for an optimal OA joint repair should promote regenerative properties of chondrocytes and fight destructive effects of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that IA corticosteroids have positive short-term effects on pain in knee OA and are widely used by clinicians, significant variation in the magnitude of the response has been reported. 57 Pain improvement using a visual analog scale on a 0 to 100 scale has demonstrated mean changes ranging from 16.2 to 35.7 mm reported in a recent systematic review. 58 Yu and Hunter (2016) also cited the pain experience by individuals with OA to involve a complicated biopsychosocial model that involves catabolic and inflammatory cytokines and sensitization of nociceptive pathways by the activation of primary efferent nerves in response to inflammation or tissue injury.…”
Section: Factors That Might Affect a Response To Intra-articular Cortmentioning
confidence: 98%
“…58 Yu and Hunter (2016) also cited the pain experience by individuals with OA to involve a complicated biopsychosocial model that involves catabolic and inflammatory cytokines and sensitization of nociceptive pathways by the activation of primary efferent nerves in response to inflammation or tissue injury. 57 The relationship of pain to structural damage is very complicated and the concepts of differences in central perception exacerbate this poor relationship (►Table 6).…”
Section: Factors That Might Affect a Response To Intra-articular Cortmentioning
confidence: 99%